Globalization and entrepreneurship - Marković, Mirjana Radović, author. Link
1 online resource.
Keywords: "Globalization and Entrepreneurship explores the transformative impact of digital technologies on entrepreneurship across three distinct, but interconnected nations. It presents a comprehensive analysis of how digital advancements and AI are reshaping traditional business models and fostering economic growth in China, Japan, and Bangladesh. With its focus on emerging trends and practical case studies, this book offers a thorough exploration of digital entrepreneurship's role in driving innovation and addressing socioeconomic challenges in these regions. Readers will benefit from a multi-dimensional view of globalization's effects on entrepreneurship, highlighting the unique contributions and interactions of China, Japan, and Bangladesh. The book examines the influence of digital transformation, AI, and globalization on business practices and economic development. It provides valuable insights into how different countries are adapting to and leveraging technological advancements for competitive advantage, offering actionable recommendations for policymakers, business leaders, and scholars interested in the future of global entrepreneurship. It is essential reading for academics, researchers, and practitioners in international business, digital entrepreneurship, and global economic studies. It is particularly useful for those interested in the strategic and practical implications of digital technologies in diverse economic contexts. Whether you are a scholar seeking to understand global entrepreneurial dynamics or a business leader aiming to navigate the complexities of international markets, this book offers critical insights into the evolving landscape of global entrepreneurship"--